1968
DOI: 10.2307/1936543
|View full text |Cite
|
Sign up to set email alerts
|

Germiantion Requirements of the Desert Shrub Larrea Divaricata

Abstract: Germination requirements of Larrea divaricata Cav. were studied in the laboratory using seed collected at 34 United States sites. Collection sites were grouped into three desert regions (Chihuahuan, Sonoran, Mojave) of increasing aridity from east to west. Optimum laboratory conditions for germination were: darkness, 23°C, leaching the mericarps with running water, wetting and drying cycles, exposure to cold temperatures prior to sowing, and maintaining the medium about the seeds near—zero in osmotic pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
1
4

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 8 publications
9
103
1
4
Order By: Relevance
“…It is probable that root and plumule lengths are manifestations of the earliness of germination because seeds from the basal region germinated earlier and produced longer roots and plumule than the apical ones. This agrees with the report of Barbour (1968) that longer roots are indicative of the speed of germination. In addition, Oladiran and Mumford (1985) reported that large (more mature) Amaranthus seeds germinated earlier and produced longer seedlings than small seeds.…”
Section: Discussionsupporting
confidence: 93%
“…It is probable that root and plumule lengths are manifestations of the earliness of germination because seeds from the basal region germinated earlier and produced longer roots and plumule than the apical ones. This agrees with the report of Barbour (1968) that longer roots are indicative of the speed of germination. In addition, Oladiran and Mumford (1985) reported that large (more mature) Amaranthus seeds germinated earlier and produced longer seedlings than small seeds.…”
Section: Discussionsupporting
confidence: 93%
“…The apparent uniform spatial distribution of desert plants stimulated a large number of ecological studies of spatial pattern within and among desert plant species (Greig-Smith and Chadwick 1965, Beals 1968, Barbour 1969, Woodell et al 1969, Anderson 1971, Cody 1986, Manning and Barbour 1988 and of the nature of interactions among neighboring plants (e.g., Turner et al 1966, Barbour 1973, Yeaton and Cody 1976, Steenbergh and Lowe 1977, Wright 1982, McAuliffe and Janzen 1986, Manning and Barbour 1988, McAuliffe 1988, Brisson and Reynolds 1994, Holzapfel and Mahall 1999. These studies illustrate the extent that spatial pattern may or may not reflect direct interactions among neighboring plants.…”
Section: Neighbor Effectsmentioning
confidence: 98%
“…Desert plant communities provide a convenient system in which to study neighbor effects because species assemblages are small, and a large literature associates the spatial distributions of desert plants with plantplant interactions (Beals 1968, Barbour 1969, 1973, Yeaton and Cody 1976, Fonteyn and Mahall 1981. Competition among plants tends to exclude neighbors, and, in time, can promote uniform spatial patterns (Beals 1968, Phillips and MacMahon 1981, Ehleringer 1984, McAuliffe and Janzen 1986, Manning and Barbour 1988.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean plant densities were 20 and 22 plants/m2 at the August and October census dates, respectively. Data on temperatures required for germination for seven of the cool-season species were found in the literature (Barbour 1968;Booth 1992;Chatterton and McKell 1969;Griffith and Booth 1998;Jones and Nielson 1992;Jordan and Haferkarnp 1989;Kay et al 1977a;Kay et al 1977b;Meyer et al 1998;Potter et al 1986;Romo and Eddleman 1988;Sheps 1973;Wood et al 1976). For these seven species, the number of days that soil temperatures were within a favorable range for germination decreased from the December seeding by an average of 8, 19, and 23 days for the TDR-MGR-EV-000007 REV.…”
Section: October Census: Cool-season Speciesmentioning
confidence: 99%